Secondary ice production upon freezing of freely falling drizzle droplets - Keinert, Alice; Spannagel, Dominik; Leisner, Thomas; Kiselev, Alexei (Journal of the atmospheric sciences, 2020)
Ice multiplication processes are known to be responsible for the higher concentration of ice particles versus ice nucleating particles in clouds, but the exact secondary ice formation mechanisms remain to be quantified. Recent in-cloud observations and modeling studies have suggested the importance of secondary ice production upon shattering of freezing drizzle droplets. In one of our previous studies, four categories of secondary ice formation during freezing of supercooled droplets have been identified: breakup, cracking, jetting, and bubble bursts. In this work, we extend the study to include pure water and an aqueous solution of analog sea salt drizzle droplets moving at terminal velocity with respect to the surrounding cold humid air. We observe an enhancement in the droplet shattering probability as compared to the stagnant air conditions used in the previous study. Under free-fall conditions, bubble bursts are the most common secondary ice production mode in sea salt drizzle droplets, while droplet fragmentation controls the secondary ice production in pure water droplets.